Contextual, emotional and behavioural influences of YouTube product review videos and official advertisements on consumers - Aditya Athni (Journal of Applied Leadership and Management, 2017)
Research Question: In comparing product review videos to official advertisements on YouTube, what type of video has a stronger contextual, emotional and behavioural influence on consumers? Methods: Empirical study by means of an online survey, based on a comparative approach, to gauge consumer perceptions upon exposure to both product review videos and official advertisements on YouTube. Results: YouTube product review videos are found to have a stronger contextual, emotional and behav-ioural influence on consumers as compared to official advertisements.
Keywords: 650; YouTube; behaviour; influence; consumer